Checking spanning trees optimality using associative parallel processors and its visualization - Nepomniaschaya, A.S.; Borets, T.V. (Інститут програмних систем НАН України, 2004)
In this paper, by means of an abstract model of the SIMD type with vertical data processing (the STAR-machine), we present a simple associative parallel algorithm for implementing the criterion of Chin and Houck to verify minimal spanning trees in undirected graphs. This algorithm is given as the corresponding STAR procedure CST whose correctness is proved and time complexity is evaluated. We also provide an experiment of verifying two spanning trees for optimality in a given undirected graph.